Multiple paternity in the starry smooth‐hound shark Mustelus asterias (Carcharhiniformes: Triakidae). (29th October 2013) - Farrell, Edward D.; O'Sullivan, Niall; Sacchi, Carlotta; Mariani, Stefano
<x xml:space="preserve">Abstract</x> Multiple paternity was investigated in the starry smooth‐hound shark, Mustelus asterias Cloquet, 1821. Analysis of 12 pregnant females and their embryos, at four microsatellite loci, showed that at least 58% carried multiply‐sired litters. Paternal skew was observed, with one male siring most of the embryos within a litter, although no patterns of association were detected between the identity of the father and the size or the uterine position of the embryos. Sperm storage was observed in the oviducal glands of all twelve females. Results shed light on the complexity of reproductive strategies and selective processes in M. asterias. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 119–125.